A Unified Analysis of English Passive Voice and Aspects - Dwijatmoko, Benedictus B. (Widya Mandala Catholic University Surabaya, 2019)
English passive voice and aspects are generated in the same process and have the same D-structure. In a passive sentence, progressive sentence, and perfect sentence, T (tense) takes a VP headed by be or have, and be or have takes a Participle Phrase (PartP), and –en or –ingtakes a VP as its complement. Be or have in the upper VP merges with T, and the verb in the lower VP merges with Part. The specifier or complement of the lower VP moves cyclicly through the specifier of Part and the specifier of the upper verb to occupy the subject position. The single theory on the production of passive, progressive, and perfect sentences observes the principle of economy of derivation and, therefore, contributes to the explanation of the relative easiness of a child in acquiring his or her mother tongue.